PENDIDIKAN NONFORMAL (PNF) BAGI PENGEMBANGAN SOSIAL - Sodiq A Kuntoro (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2006)
Nonformal education activities are often implemented as practical education or training for the purpose to cope with economic problems of the individual learners. This economic orientation causes the other aspect of nonformal education aims such as social and cultural aspects are neglected. If nonformal education is considered in more wider as a mean for achieving the realization of lifelong education in society, the current emphasis of its purposes needed to enlarge. Nonformal education should not aimed to cope with economic problems only, but also to develop the social and cultural aspect of people life.